Pedagogical Erosion Guru Pendidikan Agama Islam di Era Kecerdasan Buatan - Roisul Falah; Ifada Retno Ekaningrum; Nur Cholid; Ghufron Hamzah (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Agama Islam Nahdlatul Wathan Samawa Sumbawa Besar, 2026)
The advancement of artificial intelligence in education has brought efficiency to Islamic Religious Education teachers, yet it also poses the risk of pedagogical erosion, namely the gradual weakening of teachers’ pedagogical capacity due to excessive dependence on AI. The main problem addressed in this article lies in the absence of studies that specifically interpret pedagogical erosion in the context of Islamic Religious Education learning and connect it with Ibnu Qayyim al-Jawziyyah’s concept of tarbiyah ruhaniyah. This study aims to explain the meaning of pedagogical erosion in Islamic Religious Education learning and to identify the dimensions of tarbiyah ruhaniyah that are most vulnerable to erosion as the use of AI increases. The method used is a narrative literature review conducted through three stages of analysis: literature mapping, critical synthesis, and the construction of conceptual arguments. The findings show that pedagogical erosion in the context of Islamic Religious Education is not merely the weakening of teachers’ technical competence, but the erosion of teachers’ capacity as murabbi who carry out tazkiyatun nafs, taqwiyat al-iman, muraqabah, and mujahadah through uswah hasanah. The dimension most vulnerable to erosion is tazkiyatun nafs, followed by uswah hasanah, muraqabah, mujahadah, and taqwiyat al-iman. In conclusion, the use of AI in Islamic Religious Education learning needs to be guided by pedagogical and theological awareness so that it does not replace the teacher’s human presence, which is the core of tarbiyah ruhaniyah.